2016
DOI: 10.1055/s-0035-1561636
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach for Enantio- and Diastereocontrol in the Synthesis of 2,3-Disubstituted Succinic Acid Esters: Synthesis of the pan-Notch Inhibitor BMS-906024

Abstract: An oxidative intermolecular enolate heterocoupling reaction was employed for the synthesis of anti-2,3-disubstituted succinic acid mono-and differentially protected diesters. Tactical approaches to access all the diastereomers are discussed. The method was applied to the synthesis of a potent anticancer agent, BMS-906024.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Moreover, oxidative enolate heterocoupling has found use in both industrial and academic circles. For instance, Gavai and co-workers from Bristol-Myers Squibb used this method to synthesize a series of anticancer agents such as BMS-906024 ( 29 ) (currently in phase II clinical trials) . The groups of Overman, , Tang, Nicolaou, Yang, and Thomson , have applied this approach to the syntheses of (−)-actino­phyllic acid ( 30 ), spiro­bacillene A ( 31 ), furano­cembranoid precursors such as 32 , (+)-propindi­lactone G ( 33 ), and metacyclo­prodigiosin ( 34 ), and propolis­benzofuran B ( 35 ), respectively.…”
Section: A Radical Start: Oxidative Enolate Couplingmentioning
confidence: 99%
“…Moreover, oxidative enolate heterocoupling has found use in both industrial and academic circles. For instance, Gavai and co-workers from Bristol-Myers Squibb used this method to synthesize a series of anticancer agents such as BMS-906024 ( 29 ) (currently in phase II clinical trials) . The groups of Overman, , Tang, Nicolaou, Yang, and Thomson , have applied this approach to the syntheses of (−)-actino­phyllic acid ( 30 ), spiro­bacillene A ( 31 ), furano­cembranoid precursors such as 32 , (+)-propindi­lactone G ( 33 ), and metacyclo­prodigiosin ( 34 ), and propolis­benzofuran B ( 35 ), respectively.…”
Section: A Radical Start: Oxidative Enolate Couplingmentioning
confidence: 99%
“…Within this context, oxidative enolate coupling has emerged as a powerful tool for accessing complex molecular architectures, , as highlighted by a number of recent total syntheses employing the reaction. While the earliest example of oxidative enolate coupling dates back to 1935, the 1970s saw the advent of synthetically useful variants due to the pioneering contributions from the laboratories of both Rathke and Saegusa. , Recent years have seen a reinvigoration of interest in methods for achieving oxidative enolate coupling. For example, in 2006, Baran and DeMartino introduced new methods for the oxidative cross-coupling of amide- and ketone-derived enolates. , Flowers and Casey studied the oxidative cross-coupling of two ketone-derived lithium enolates and concluded that efficient cross-coupling resulted from favorable formation of heteroaggregates in solution .…”
Section: Introductionmentioning
confidence: 99%
“…Under certain conditions where no external nucleophile is present, the silyl enol ether undergoes dimerization to generate a 1,4-dicarbonyl compound. This result is of particular interest because although several different approaches have been previously described for the synthesis of this compound class, notably the oxidative heterocoupling of lithium enolates by Baran and co-workers (Figure c), flexible methods still remain scarce. In particular, homocoupling is a typical problem of oxidative strategies, while quaternary center formation is often not possible.…”
mentioning
confidence: 99%